PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA DENGAN MEMANFAATKAN APLIKASI BUKU WARUNG PADA UMKM DI KELURAHAN SEPANJANG - Wicaksono, Achmad; Susilo, Achmadi; Thohiron, Mochamad; Joeniarti, Elika (Universitas Sanata Dharma, 2023)
MSMEs are the backbone of the economy in many countries, including Indonesia. In facing increasingly fierce competition and dynamic changes in the business environment, the preparation of financial reports is important for MSME players. The purpose of holding this community service activity is to help MSMEs in optimizing the use of information technology to manage business finances. This training activity was held at the Sepanjang Village Office in July 2023. The method used in this training was the lecture method and practice using applications. The training results showed that all MSME actors present were able to compile simple financial reports using the Buku Warung application. Through the preparation of these simple financial reports, MSME actors can make better business decisions than before.